Manic Histories: The Gendered Aesthetics of Hysterical Realism in the Works of Jennifer Egan and Zadie Smith (The International Journal for Scientific Research, 2026)
This research reevaluates the literary mode of "Hysterical Realism" through the lens of New Historicism, arguing that its characteristic narrative excess serves as a sophisticated "somatic archive" for marginalized histories. While traditionally critiqued as a hollow stylistic device, this paper posits that in the works of Jennifer Egan and Zadie Smith, the hysterical mode functions as a vital epistemological tool to bridge the fracture between female interiority and the external pressures of history. Through a comparative analysis of Smith’s White Teeth and The Fraud alongside Egan’s Manhattan Beach, the study explores how post-colonial "symptoms" and "technological hysteria" allow protagonists to negotiate social erasure. By synthesizing New Materialism and contemporary theories of hysteria, the research concludes that Smith and Egan transform the "hystericized" text into a counter-archive, reclaiming the female psyche from the margins and establishing "maximalism" as a rational aesthetic response to the complexities of the historical "real."
Keywords: Hysterical Realism; New Historicism; Counter-Archive; Female Agency; Somatic Narrative